Pengaruh Jenis Makanan Tambahan Berbasis Pangan Lokal terhadap Pertumbuhan Tinggi Badan Balita Stunting di Kabupaten Semarang - Zulaikhah, Siti; Zulaekah, Siti; Kusumawati, Sary; Rahmawati, Hanik (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Stunted refers to a growth disorder that can progress into stunting if not addressed promptly. This condition impacts children's linear growth but can still be improved through appropriate nutritional interventions and proper management support. Objective: This study aimed to analyze the effect of different forms of supplementary feeding based on local food sources on the increase in height of stunted toddlers in Semarang Regency. This research employed a quantitative method with a quasi-experimental design using a pretest-posttest two-group approach. A total of 20 stunted toddlers aged 12–59 months were selected through purposive sampling, with 10 subjects assigned to the regular food-based PMT group and 10 subjects to the enteral food-based PMT group. Results: In the regular food-based PMT group, the average height increased from 83.6 cm to 84.4 cm (p = 0.033), while in the enteral PMT group, the average height increased from 81.2 cm to 81.7 cm (p = 0.035). The mean increase in height was 0.8 cm for the regular food-based PMT group and 0.5 cm for the enteral PMT group. The Mann-Whitney U Test showed a p-value of 0.300, indicating no significant difference between the two groups. However, descriptively, the regular food-based PMT group exhibited a higher average increase compared to the enteral PMT group. Supplementary feeding in both regular and enteral food-based forms derived from local food sources was effective in increasing the height of stunted toddlers. However, no significant difference in effectiveness was found between the two forms of PMT within the two-week intervention period.